Triple comorbidity of severe mental illness, HIV infection & alcohol abuse in a female population at a community psychiatric clinic in Cape Town: Prevalence and correlates - Mgweba-Bewana, Lihle (Department of Psychiatry and Mental Health, 2018)
Introduction: Severe mental illness (SMI), Human immunodeficiency virus (HIV) infection and hazardous alcohol use are global epidemics. Each condition is independently associated with significant adverse health outcomes. The presence of two or more of these conditions in one individual may result in worse health outcomes. A key mediator of poor health outcomes are factors such as medication adherence. In resource-limited countries like South Africa, the impact of psycho-social factors may contribute further to worse health outcomes. These factors include poverty and unemployment; as well as gender. In South Africa, proportionately more women are infected with HIV than men; and they are also vulnerable to the problems of trauma and interpersonal violence. The main aim of this study was to investigate the prevalence of a triple co-morbidity of SMI, HIV infection and hazardous alcohol use in a female population at a community psychiatric clinic in Cape Town South Africa; and the impact of this triple comorbidity on medication adherence. Furthermore, we set out to identify demographic and clinical variables that are predictors of poor adherence to both psychotropic medication and ART where applicable. Methods: We conducted a cross-sectional study of female patients presenting to Gugulethu psychiatric clinic over a ten-month period. Demographics and clinical variables were explored using the Alcohol Use Disorders Identification Test (AUDIT); the adapted Morisky Scale to Assess Adherence to Psychotropic Medications; and an adherence to HIV antiretroviral treatment self-assessment instrument. A descriptive analysis of the demographic and predictor variables was undertaken to explore the prevalence of concurrent HIV infection and hazardous alcohol use in out-patients with SMI; as well as to investigate whether co-morbidity is associated with poor levels of adherence to psychotropic medication, as well as antiretroviral treatment (ART) in HIV positive patients. Results: We interviewed 127 patients, of whom 55 were HIV positive (43.3%). The overall prevalence of a triple comorbidity in this population was 7.9%. Only 20% within this triple comorbidity group were adherent to their psychotropic medication. Out of the 10 participants with a triple comorbidity, only five were on ART. Of these 5 participants, only two were adherent. Individuals with hazardous alcohol use were less adherent to psychotropic medication compared to those without. The seven respondents in the dual diagnosis group (SMI and hazardous alcohol use) had the lowest overall psychotropic adherence levels compared to the other subgroups (0%). Furthermore, concurrent hazardous alcohol use predicted poorer levels of compliance to ART for those with HIV infection. Conclusion: The presence of a triple diagnosis was not found to be a predictor of poorer medication adherence, compared to having one or two diagnoses. Nevertheless, there was evidence that concurrent hazardous drinking in SMI patients predicted poor compliance to both psychotropic and ART treatment regimens (for those living with HIV). These patients should be supported in future interventions to improve medication adherence and reduce hazardous drinking.